Սիմին Դանեշվար. Նախահեղափոխական սոցիալական հիմնահարցերից մինչև հետհեղափոխական ֆեմինիզմ - Սաֆրաստյան, Լիլիթ («Զանգակ - 97»)
One of the most renowned contemporary Iranian women writers Simin Daneshvar has startcd to write and publish in the pre-revolutionary era. Her creative years coincide with the sociopolilical events of the early 1960s, which have had subslantial effects on her works. Pre-revolutionary social climate, contributed to the formation of Daneshvar's general ideological views. Daneshvar gained tremendous success with her novel "Savushun", published in 1969, the first novel ever written by Iranian women. "Savushun" became a best-seller for over two decades being reprinted fifteen times.
Keywords: Իրանական գրականություն; Մատենագիտություն